Manejos de agroquímicos en el cultivo de maíz duro y su efecto ambiental en el humedal abras de mantequilla cantón Vinces año 2019 - Santillán Muñoz, Olimpa Betzabeth (2019)
The indiscriminate use of agrochemicals, from its origin to the present has produced a large number of environmental effects, such as air pollution, both surface and ground water, soil affecting its structure and the different organisms of both the flora and the fauna that live in it. The objective of this research is to evaluate the environmental effect of the handling of the agrochemicals used in the cultivation of hard corn, in the towns of La Felicidad, Montenegro, El Recuerdo and Nuevo Amanecer of Abras de Mantequilla Wetland of the Canton of Vinces; In order to arrive at what was proposed, the methodology used was the application of surveys to farmers in the area under study. An environmental impact assessment was also carried out through the use of agrochemicals through an index called Environmental Qualification, the which allowed to determine by scales the affectation to the environment, soil samples were taken to assess their physico-chemical properties, both in the cultivation of corn and in uncultivated soil, and finally weeds were identified that were in the study areas. From the results it can be shown that agrochemicals cause very high environmental impacts in the fauna of the soil and water, and even in the health of those who use these products and that if mitigation measures are not taken, species of the flora and fauna and even ecosystems that are of great importance for the maintenance of biodiversity. Keywords: agrochemicals, environmental impact, fauna, flora, soil, water